2021
DOI: 10.1016/j.jinf.2021.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the timeliness of antibiotic therapy on the outcome of patients with sepsis and septic shock

Abstract: Objectives: To review the impact of the timeliness of antibiotic therapy on the outcome of patients with sepsis or septic shock. Methods: We searched MEDLINE, EMBASE, the Cochrane Library, Web of Science, Open-SIGLE databases, ClinicalTrials.gov and the metaRegister of Controlled Trials on July 27, 2020 for relevant studies on the timing of antibiotic therapy in adult patients with sepsis or septic shock. The primary outcome measure was all-cause crude or adjusted mortality at reported time points. Results: We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 53 publications
0
22
1
2
Order By: Relevance
“…Rapid empirical administration of antibiotics has long been a cornerstone of sepsis management ( Kang et al, 2003 ; Micek et al, 2005 ; Lodise et al, 2007 ). However, there is some controversy over whether early administration of antibiotics improves patient outcomes ( Asner et al, 2021 ). Empirical treatment can result in a sub-therapeutic dose or incorrect antibiotic choice.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid empirical administration of antibiotics has long been a cornerstone of sepsis management ( Kang et al, 2003 ; Micek et al, 2005 ; Lodise et al, 2007 ). However, there is some controversy over whether early administration of antibiotics improves patient outcomes ( Asner et al, 2021 ). Empirical treatment can result in a sub-therapeutic dose or incorrect antibiotic choice.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, obtaining blood cultures and administration of appropriate antimicrobial agents are cornerstones of sepsis management [14]. Timely and appropriately administered antimicrobial treatments from the time where patients display signs of organ dysfunction in the context of suspected or confirmed infection are significantly associated with improved patient survival [15][16][17]. Studies have shown that delayed administration of J o u r n a l P r e -p r o o f antimicrobials leads to increased mortality, risk of complications during treatment and length of hospitalisation, resulting in higher medical costs [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the criteria for selecting an antibiotic depend on the site of infection and/or the organs affected [ 20 ]. Consequently, the mortality sharply increases as the initial response time is delayed [ 21 ]. For these reasons, the development of new methods for sepsis diagnosis and alternative therapies to control systemic inflammatory reactions is an intense research focus.…”
Section: Introductionmentioning
confidence: 99%